Stepping from College Classrooms to the Political Front. The Emergence of Feminism in the Norwegian Maoist Movement before 1973 - Gęsiarz, Michał (Folia Scandinavica Posnaniensia, 2023)
The aim of this article is to investigate the origins of the Women’s Front, a women’s movement co-founded by Norwegian Maoists in the 1970s. The analysis seeks to capture the dynamics of women’s activism in relation to the broader political landscape and, concurrently, to understand the Women’s Front in a broader temporal perspective. The sources used were newspapers and publications issued by different branches of the Norwegian Maoist movement. Women’s politics are analysed both as a grassroots phenomenon and a part of agitation which emerged under the 1972 anti-EEC campaign. This makes it possible to show how women’s politics found a place on the agenda of Norwegian Maoism and what kind of obstacles it had to face on its way to gaining autonomy. The patterns of feminist mobilisation demonstrated by this analysis can make a contribution to the broader debate on the role and place of feminism in traditional political structures.